Investigation on Dielectric Properties of Sludge Waste from Water Treatment Using Microwave Non-Destructive Testing (MNDT) - Zable, M. A. H.; Ismail Khan, Z.; Zakaria, N. A.; Abd Rashid, N. E.; Ismail Khan, N.; Mahmood, M. K. A.; Ghodgaonkar, D. K. (International Journal of Integrated Engineering, 2023)
The demand for water cleanup rises in tandem with a country's requirements and development. Recovery of purified water containing nutrients and other beneficial materials is a critical opportunity that must be taken advantage of. A challenge that needs to be tackled is the necessity for large capacity and high-value management of sludge waste following the water treatment process. The pH level and microwave frequencies influence were used as a starting point for assessing the content of the sludge waste. Microwave non-destructive testing (MNDT) is a microwave measurement that can be used to determine the dielectric characteristics of materials without destroying or modifying the sample's content. The methodology employs a free-space measurement technique with a frequency range of 8 to 12 GHz (X-band). Through S-parameters acquired, a correlation analysis was done to analyze the effect of frequencies with the sludge waste. A comparative investigation with peat soil samples in establishing if the sludge has similar attributes to normal soil is used to ensure the accuracy of the sludge waste data. It can be determined that the sludge waste has a high signal correlation towards the frequency band 8 GHz to 12 GHz, which is compatible with the MNDT approach. All of the sludge samples had a pH range that is appropriate for agricultural use.